Fancy bioisosteres: synthesis and dopaminergic properties of the endiyne FAUC 88 as a novel non-aromatic D3 agonist - Gmeiner, Peter; Hübner, Harald; et al. (Bioorganic & Medicinal Chemistry, 2005)
Enlargement of the π-electronic system of the non-aromatic D3 agonist FAUC 73 led to dopaminergic endiynes of type 1 being synthesized via the bromovinyl triflate 7a as a key intermediate when palladium catalyzed coupling reactions were exploited for the introduction of the (aza)alkyne substituents. As the first neuroreceptor active endiyne, FAUC 88 (1c) displayed high and selective dopamine D3 receptor affinity (K i high = 3.2 nM) and substantial ligand efficacy (72%, EC 50 = 2.5 nM). Similarities between molecular electrostatic potentials induced by the catechol subunit of the genuine neurotransmitter and those of its non-aromatic endiyne bioisostere are discussed. © 2004 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.nat.dchph.lphch.fancyb_5